An Example of Domestic Mamluk Architecture in Damascus (14th and 15th centuries) - Fayyad, Imane (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
The al-Kawā residence is located in one of the districts of Damascus old town within the town walls, and it has kept a lot of noticeable traces from older times. The residence is two-levelled. The ground floor is made up of an inner yard around which the living and reception rooms are situated, as well as an īwān, a small cellar and outbuildings. The yard of the house now offers two remarkable front walls, south and north, built-in white calcareous stones and black basalt. They are decorated with panels showing geometric patterns, probably going back to the Mamluk period (14th-15th centuries). Both façades are not compatible with the eastern and western front walls of the house, which seem to have been constructed at a later period (18th to 19th centuries).